Insights into parental perspectives: Children's eye care in Saudi Arabia - Sokinah N. Al Musalami; Reem J. Al Qasim; Bayan S. Alshuhayb; Abdulaziz I. Al-Somali (Heliyon)
Purpose: Despite the concerning growth in the number of children with preventable or treatable causes of blindness, parents and/or children often do not notice many eye problems due to the lack of adequate knowledge about them. Considering the lack of updated relevant literature on this topic, this study aimed to gain insights into parental perspectives regarding children's eye health and the barriers that prevent them from promptly addressing these issues. Methods: A cross-sectional online survey was randomly distributed to Saudi parents of children aged 0–18 years from February 2022 to April 2022. Results: A total of 1265 parents (mean age = 36.10 ± 10.043 years) completed the questionnaire, and 61.3 % obtained high knowledge scores. The factors associated with high knowledge scores included an educational level above high school, employment in the healthcare industry, and having a child with an eye disease.Two-thirds of the parents did not take their children for periodic eye examinations. However, parents from the central region, healthcare workers, and those having a child with an eye disease were more likely to have their children's eyes checked regularly. Moreover, 40 % of parents tended to believe that routine eye checkups were unnecessary if their children had seemingly normal eyes and no eye complaints.Concerning corrective spectacle use, parents from the northern region and those with an educational level of high school or less were more likely to reject it. Our findings also showed that 25 % of parents believed that eyeglasses may limit their children's daily activities. Conclusion: Parental knowledge of children's eye care in Saudi Arabia was acceptable.